PENERAPAN METODE FUZZY ANALYTICAL HIERARCHY PROCESS DALAM MENENTUKAN PRIORITAS KEBUTUHAN PENGEMBANGAN UMKM KOPI GANJARESIK - Arvy Renardi, - (2019)
Competition is so tight in the industrial world that requires taking the right step in a decision to get good results efficiently. To develop a business needs the right initial steps for rapid development. There are still many needs that are needed by MSME Coffe Ganjaresik to develop its business. The purpose of this study was to determine the priority level of development needs of the Coffe Ganjaresik MSME. Based on the results of research on experts, there were 6 criteria and 17 sub-criteria needed to develop the business. The first step after data collection is to determine the consistency of the data using the AHP method. The results of the consistency test produce data that is consistent across all data. Fuzzy AHP method is used to reduce the level of subjectivity of the data taken. The last step is to determine the priority of development needs using the Fuzzy AHP method. The highest priority in the criteria is farmers while the subcriteria are education and training